Three-dimensional numerical modelling and analysis of complex stress variations and deformations at Malmberget mine, Sweden - Saiang, David; Jones, TH (Caving 2022: Fifth International Conference on Block and Sublevel Caving, 2022)
LKAB’s Malmberget mine is not only one of the largest SLC mines in the world, but it is also one of the most complex, where between 10 and 15 orebodies are mined simultaneously. The subvertical orebodies are generally stacked, where one orebody is on the footwall or the hangingwall of the other. This results in complex stress interactions and deformation patterns when these orebodies are mined simultaneously. Keeping the entries into the respective orebodies open is a critical part of daily mine planning at the Malmberget mine and the ability to predict stress changes and associated damage to these entries contributes significantly to this planning. To develop an effective empirical tool for predicting mining-induced stress changes and associated entry deformation and damage, a two-year monitoring program was initiated in 2019 to record those stress changes and their consequences. These results are described in other papers written by the authors for this same symposium. This paper, however, focuses on the numerical modelling component of this work, where a series of numerical modelling was done using FLAC3D with monitoring data as the basis for model calibrations. Given the extent of the mining operations at Malmberget mine, the stress changes are global in extent on the scale of kilometres and extend from 100 to 200 m below the active mining front. The field data collected in the entries are local and do not necessarily reflect the global extent of stress changes. Nevertheless, through numerical modelling it is possible to build a global model to observe stress changes and the resulting deformations as neighbouring orebodies are mined. Funder: Luossavaara Kiirunavaara AB; ISBN för värdpublikation: 978-0-6450938-3-4